Gestational diabetes causes hyperactivity of the sympathetic nervous system and hypertension in adult mice offspring - Li Yang; Xingyu Zhu; Jun Zhu; Zegang Hu; Chunxiang Wang; Hao Luo; Xue Bai (Clinical and Experimental Hypertension)
Background Gestational diabetes can lead to increased blood pressure in offspring, accompanied by impaired renal sodium excretion function and vasoconstriction and diastole dysfunction. However, there are few studies on whether it is accompanied by increased sympathetic nerve activity.Methods Pregnant C57BL/6 mice were intraperitoneally injected with streptozotocin (35 mg/kg) or citrate buffer at day 0 of gestation. The mice of control mother offspring (CMO) and diabetic mother offspring (DMO) at 16 weeks of age were infused with vehicle (artificial cerebrospinal fluid, aCSF, 0.4 μL/h) or tempol (1 mmol/L, 0.4 μL/h) into the bilateral paraventricular nucleus (PVN) of mice for 4 weeks, respectively.Results Compared with CMO group, SBP and peripheral sympathetic nerve activity (increased heart rate, LF/HF and plasma norepinephrine and decreased SDNN and RMSSD) were increased in DMO group, which was accompanied by increased angiotensin II type-1 receptor (AT1R) expression and function in PVN. The increase in AT1R expression levels was attributed to a decrease in the methylation level of the AT1R promoter region, resulting in an increase in AT1R mRNA levels in PVN of DMO. Moreover, compared with CMO group, the levels of oxidative stress were increased and DNMT1 expression was decreased in PVN of DMO. Bilateral PVN infusion of tempol attenuated oxidative stress increased the level of DNMT1 expression and the binding of DNMT1 to the AT1R promoter region, which reduced mRNA and protein expression level of AT1R, heart rate and SBP in DMO, but not in CMO.Conclusions The present study provides evidence for overactive sympathetic nervous systems in the pathogenesis of gestational diabetes-induced hypertension in offspring. Central antioxidant intervention in the PVN may be an important treatment strategy for fetal-programmed hypertension.